Lingual CD36 and nutritional status differentially regulate fat preference in obesity-prone and obesity-resistant rats - Braymer, H. Douglas (Physiol Behav, 2017)
Lingual fatty acid receptors (i.e. CD36) mediate the orosensory perception of fat/fatty acids and may contribute to the susceptibility to develop obesity. The current study tested the hypothesis that fat/fatty acid preference in obesity-prone (OP, Osborne-Mendel) and obesity-resistant (OR, S5B/Pl) rats is mediated by nutritional status and lingual CD36. To determine if nutritional status affected linoleic acid (LA) preference in OP and OR rats, rats were either fasted overnight or fed a high fat diet (60% kcal from fat). In OR rats, fasting increased the preference for higher concentrations of LA (1.0%), while consumption of a high fat diet decreased LA preference. In OP rats, fasting increased the preference for lower concentrations of LA (0.25%), however high fat diet consumption did not alter LA preference. To determine if lingual CD36 mediated the effects of an overnight fast on LA preference, the expression of lingual CD36 mRNA was assessed and the effect of lingual application of CD36 siRNA on LA preference was determined. Fasting increased lingual CD36 mRNA expression in OR rats, but failed to alter lingual CD36 mRNA in OP rats. Following an overnight fast, application of lingual CD36 siRNA led to a decrease in LA preference in OR, but not OP rats. Lingual application of CD36 siRNA was also used to determine if lingual CD36 mediated the intake and preference for a high fat diet in OP and OR rats. CD36 siRNA decreased the preference and intake of high fat diet in OR rats, but not OP rats. The results from this study suggest that the dysregulation of lingual CD36 in OP rats is a potential factor leading to increased fat intake and fat preference and an enhanced susceptibility to develop obesity.